The effect of shareholder activism on earnings management: Evidence from shareholder proposals - Ng, Jeffrey; Wu, Hong; Zhai, Weihuan; Zhao, Jing (Journal of Corporate Finance, 2021)
We find that in general, both accrual-based and real earnings management decrease after the passage of shareholder-sponsored governance proposals. However, when accounting for the type of proposal, we observe significant heterogeneity in the effects on earnings management. Specifically, proposals focused on changing the governance structure (e.g., board independence) lead to reductions in both types of earnings management, whereas proposals specifically targeted at improving financial reporting quality lead to decreased accrual-based earnings management but increased real earnings management. The results suggest that constraints on accrual-based earnings management induce a shift toward real earnings management. Our paper indicates that the nature of the shareholder proposal has a significant impact on shareholder intervention.